Efektifitas Teknik Terapi Seni Rupa Untuk Mengurangi Kecemasan Akademik Siswa SMP - Isnaini Rizki Hidayatunnisa; Masyitoh, Dewi; Mawaddati, Ika Romika (Institut Agama Islam Negeri Curup, 2025)
Academic anxiety is a condition when someone, especially students, feels anxious, worried, or afraid when facing assessments or learning examinations. This feeling is often accompanied by physical symptoms such as palpitations, excessive sweating, or tense muscles, and psychological symptoms such as anxiety, unable to concentrate, and fear failure. This study aims to test the effectiveness of fine arts therapy in reducing the academic anxiety of class VII students at SMP IT Grafika Pesanggaran. The research design used is pre-experimental with the one group pretest-posttest approach, involving 30 students who are chosen purposive sampling. Data were collected using academic anxiety questionnaires, unstructured interviews, and field notes. Fine art therapy is held for 6 sessions in 2 weeks, which involves activities such as free drawing, collage, and expressive paintings, which are designed to help students express their feelings creatively. The Wilcoxon test results showed a significant decrease in student academic anxiety scores, with the value of Z = -2,524 (p = 0.012), indicating the effectiveness of art therapy. Qualitative analysis also reveals positive changes in students' social and cognitive behavior after intervention. The findings of this report are expected to help suggestions for developing intervention programs available from guidance and counseling services. Students in this school are interviewed as part of the quantitative research methodology. Fine Art Therapy Techniques To reduce academic anxiety in grade VII students of SMP IT Grafika Pesanggaran